Contractual Capacity and the Conflict of Laws in Common-Law Jurisdictions (Part 2): Australasia, North America, Asia and Africa - Eesa A Fredericks (Obiter, 2020)
This series of two articles provides a comparative overview of the position in common-law jurisdictions on the conflict of laws in respect of the contractual capacity of natural persons. The comparative study is undertaken in order to provide guidelines for the future development of South African private international law. Reference is primarily made to case law and the opinions of academic authors. The legal position in the law of the United Kingdom, as the mother jurisdiction in Europe, was investigated in part 1.1 Although Scotland is a mixed civil/common-law jurisdiction, the situation in that part of the United Kingdom was also discussed.Part 2 deals with the rules and principles of private international law in respect of contractual capacity in Australasia (Australia and New Zealand), North America (the common-law provinces of Canada and the United States of America), Asia (India, Malaysia and Singapore) and Africa (Ghana and Nigeria). This part also contains a comprehensive summary of the legal position in the common-law countries, followed by ideas for the reform of South African private international law in this regard.